PENGELOLAAN SUMBER DAYA ALAM DI MATA MAHKAMAH KONSTITUSI: Analitis Kritis atas Putusan Mahkamah Konstitusi tentang Sumber Daya Alam - Mulyani, Lilis (Jurnal Masyarakat dan Budaya, 2008)
The natural resources management in Indonesia has been overburdened with problems, starting from legislation problems to the impacts of their exploitations to the people and environment. The absence of uniformed national paradigm due to overlapping and multi-interpretation legislation have worsened the problems. The establishment of the Indonesian Constitutional Court in 2004 has brought a new hope to unfold the mess. However, as this writing reveals, the “interpretation” of the Constitutional Court on different types of management of natural resources has caused the policy on natural resource management even more complicated. The “stream” that the Constitutional Court follows seems to be no different than the political economy pragmatism, which was also followed by the current government.